The Impact of Social Media Marketing on E-Purchase Decisions Using Online Food Delivery Services - Dearika Irsanyya, Kharisma; Agus Rahayu; Puspo Dewi Dirgantari; Hilda Monoarfa (Dinasti International Journal of Digital Business Management, 2023)
The development of the food delivery service platform is supported by the increasing prevalence of the internet and the high number of smartphone users, which has created a dearth of online marketing-savvy business opportunities. This study compares generations X, Y, and Z in West Java to see how influential social media marketing is on e-purchase decisions using online food delivery services. A descriptive quantitative approach was used in this study. The data was collected using a questionnaire that was distributed online via Google-form to 90 social media users from the West Java region. Based on the findings of the study and the discussion, it is evident that social media marketing variables have a favorable and significant impact on e-purchase decisions using online food delivery services.